2021
DOI: 10.1007/s00468-021-02129-4
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and anatomical responses to drought stress differ between two larch species and their hybrid

Abstract: Key Message Hybrid saplings were more reactive to soil water deficit than Japanese and European larch. European larch had hydraulically safer wood and anisohydric behavior, Japanese and hybrid larch showed isohydric strategy. Abstract Deciduous larch species could be an alternative to evergreen conifers in reforestation, but little is known about drought sensitivity of their saplings. The effect of an experimental drought on hydraulics and quantitative woo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…There has been a growing interest in the influence of the bordering pit on conifer hydraulic safety [6][7][8]. The literature extensively documents the observation of contact between the torus and the pit border in aspirated pits as a means to avoid air-seeding leakage between tracheids [9][10][11]. This phenomenon (Figure 1) was also found in a greenhouse experiment conducted at Northeast Forest University in Harbin, China, specifically investigating water stress conditions.…”
Section: Introductionmentioning
confidence: 80%
“…There has been a growing interest in the influence of the bordering pit on conifer hydraulic safety [6][7][8]. The literature extensively documents the observation of contact between the torus and the pit border in aspirated pits as a means to avoid air-seeding leakage between tracheids [9][10][11]. This phenomenon (Figure 1) was also found in a greenhouse experiment conducted at Northeast Forest University in Harbin, China, specifically investigating water stress conditions.…”
Section: Introductionmentioning
confidence: 80%
“…There are significant differences between species in the shapes of scatter plots and in the location/density of earlywood and latewood clusters, reflecting the specific features of the anatomical structure. This variability reflects species-specific features with regards not only to tree size (height), but also to ecophysiological traits and species-specific adaptations to habitat conditions [46][47][48][49]. Taking into account the estimates of the threshold value k = 0.105-0.136 obtained in this work, we can conclude that the usage of one universal rigid threshold of k, as both interpretations of the Mork criterion suggest, quite often does not reflect the actual intra-seasonal variability of the anatomical structure in conifer wood.…”
Section: Discussionmentioning
confidence: 99%
“…Microphotography was achieved with a Leica DM4000 M microscope equipped with a Leica DFC320 R2 digital camera and Leica IM 500 Image Manager image analyzing software (Leica, Wetzlar, Germany). Cell wall thickness and tracheid dimensions were measured by means of Image J software [39] in the first ten radial earlywood cell files [28] of the latest annual ring in four different locations around the stem. Lumen diameters (b) and double cell wall thickness (t) in the radial (b r , t r ) and tangential (b t , t t ) directions of 20 tracheids (Figure 1a,b) were measured.…”
Section: Wood Anatomymentioning
confidence: 99%
“…Anatomical proxies for P 50 offer the advantage that samples do not need to be fresh and that hydraulic vulnerability can be determined retrospectively for selected annual rings. The approach of relating drought response of trees to "constitutive wood anatomy" is based on works by [27,28] who found that the wood formed (often several years) before drought stress impacts the sensitivity to drought in sapwood of Picea abies and different Larix species. Drought induced dieback [27] or growth decreases [28] are more strongly related to (t/b) 2 measured in the tangential rather than in the radial direction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation